Effectiveness of Powtoon Application-Assisted Inquiry Learning on Students' Learning Interest and Understanding of Mathematical Concepts at SMKN 3 Mataram - Ririn Rahmawati; Syahrir Syahrir; Agusfianuddin Agusfianuddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the effectiveness of Inquiry Learning and the impact of Powtoon-assisted learning on students' interest in learning and understanding of mathematical concepts at SMKN 3 Mataram. The low interest in learning and understanding of mathematical concepts that persists in schools is caused by learning that tends to be conventional and does not involve students actively in the learning process. Therefore, a learning model is needed that can increase active student engagement while being supported by engaging learning media. This research uses a quantitative approach with a quasi-experimental type and a pretest-posttest nonequivalent control group. The research population was all class XI students of SMKN 3 Mataram in the 2026 academic year. The research sample consisted of two classes, namely the experimental class, which was given treatment in Inquiry Learning using Powtoon, and a control class using conventional learning. The research instruments were a learning interest questionnaire and a mathematical concept understanding test. Data analysis was conducted using prerequisite tests (normality and homogeneity tests) and hypothesis testing with the Independent Samples t-Test. The results showed that Inquiry Learning and Powtoon-assisted learning are effective in increasing students' interest in learning and understanding of mathematical concepts. This is indicated by an increase in the average score in the experimental class, which was higher than the control class, both in terms of interest in learning and understanding of mathematical concepts. Thus, it can be concluded that Inquiry Learning and Powtoon assistance are effectively used in mathematics learning to increase students' interest in learning and understanding of mathematical concepts at SMKN 3 Mataram